2018
DOI: 10.1186/s12913-018-3635-3
|View full text |Cite
|
Sign up to set email alerts
|

Improving accessibility for outpatients in specialist clinics: reducing long waiting times and waiting lists with a simple analytic approach

Abstract: BackgroundLack of resources is often cited as a reason for long waiting times and queues in health services. However, recent research indicates these problems are related to factors such as uncoordinated variation of demand and capacity, planning horizons, and lower capacity than the potential of actual resources.This study aimed to demonstrate that long waiting times and wait lists are not necessarily associated with increasing demand or changes in resources. We report how substantial reductions in waiting ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 42 publications
(36 reference statements)
1
28
0
1
Order By: Relevance
“…Singapore has established percentile targets for appointment lead-times for patients because appointment postponements are regarded as unacceptable for health care services [17]. Recent studies have shown that the accessibility for patients can be significantly improved by applying simple methods and performing barrier analyses [18].…”
Section: Discussionmentioning
confidence: 99%
“…Singapore has established percentile targets for appointment lead-times for patients because appointment postponements are regarded as unacceptable for health care services [17]. Recent studies have shown that the accessibility for patients can be significantly improved by applying simple methods and performing barrier analyses [18].…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in clinic wait times may be achieved by a variety of techniques including previsit information gathering, delegation of documentation to staff, and work-flow analysis to identify bottlenecks, among others. [22][23][24] To this end, an introspective analysis into a provider's clinic practices can help improve clinic wait times and ultimately improve patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing the disciplines of these first priority clinics will help reduce wait times in these clinics and, consequently, in the hospital. 31 One of the most important disciplines investigated in this study was physician delay. The results indicated that physician delay times positively affect patient wait time and should be considered as a key factor in designing managerial interventions.…”
Section: Research Highlightsmentioning
confidence: 99%